Incredible medical mysteries 2 transsexuals - Hunter, Stephen; Armstrong, Jane.; Galligan, Kathryn Liptrott; Ackerley, Paul.; Discovery Channel (Firm).; CineNova Productions, Inc. ([S.l. Discovery Channel], 2003)
This program tackles the challenges facing the transsexuals. For these people, the issue of gender is an issue of personal identity -- of who they are as a whole person. And that after the change, it will prove that gender is not just a sexual matter, nor a personal one, but that it involves the entire social structures.
A CineNova Productions Inc. production in association with TLC.
Distributed by CanWest Entertainment International Distribution and Minds Eye International.
Producer : Jane Armstrong ; Co-producer : Kathryn Liptrott-Galligan ; Executive producer : David Lint ; for the Discovery Channel, executive producer : Paul Don Vito.
Narrator : Paul Ackerley.
VCD.
Keywords: Transsexuals; Transsexualism; Sex change; Gender identity; Sex role